Complete hydatidiform moles are composed of paternal chromosomes and maternal mitochondria. (18th August 2018) - Pan, Zijun; Usui, Hirokazu; Sato, Asuka; Shozu, Makio
Abstract: Mitochondrial DNA (mtDNA) and genomic DNA are produced in separate subcellular compartments. Human mtDNA is transmitted via maternal transmission in general. Complete hydatidiform moles (CHMs) represent major trophoblastic diseases that are cytogenetically exceptional because the chromosomal genomic DNA is derived only from sperm cells, making them strikingly different from normal concepti. However, few reports have described the mtDNA-transmission pattern in hydatidiform moles. To evaluate mtDNA transmission in androgenetic CHMs, we compared the sequences of hypervariable regions in 16 trios sets of mtDNAs from maternal, paternal, and villous samples of androgenetic CHMs diagnosed by short tandem repeat-polymorphism analysis. All mtDNAs in androgenetic CHMs were maternally derived, in line with the general human inheritance pattern. Three maternal mtDNAs were heteroplasmic. The heterozygous status of maternal mtDNA was reflected in villous tissue, in which variants status was also heterozygous. CHMs are composed of paternal chromosomes and maternal mitochondria.